Peripheral vestibular loss in noise-exposed firefighters - Snapp, Hillary Anne; Vanlooy, Lindsey; Kuzbyt, Brianna; Kolberg, Courtney; Laffitte-Lopez, Denise; Rajguru, Suhrud (Frontiers in Integrative Neuroscience, 2023)
Occupational workers are increasingly aware of the risk of noise overexposure to the auditory system but lack awareness about potential risks to the vestibular system. The purpose of this study was to investigate changes in vestibular end organ function in a known at-risk noise-exposed population, firefighters compared to age- and sex-matched controls using electrophysiologic measures of cervical vestibular evoked myogenic potentials (cVEMP). A cross-sectional observational study compared cVEMP response characteristics in 38 noise-exposed firefighters. Firefighters were grouped by years of exposure in the fire service. The cVEMP responses were compared within firefighter groups and between firefighters and age- and sex-matched controls. Dependent variables included the response characteristics of amplitude, latency and threshold. cVEMP response amplitudes were significantly decreased in firefighters compared to their age- and sex-matched controls. Threshold of the cVEMP responses were significantly higher in firefighters compared to controls and firefighters had a higher incidence of absent cVEMP responses compared to controls. Response amplitudes decreased with increasing years in the fire-service at an increased rate compared to their age- and sex-matched controls. Latency of the cVEMP response was not significantly different in firefighters compared to controls. These findings are consistent with both animal and human studies suggesting noise-induced changes in the sacculocollic pathway. In the absence of any reported vestibular symptoms or auditory indicators of noise-induced hearing loss, these early effects on the vestibular system point to a potential hidden vestibular loss.